Стратегические изменения характера управления предприятием в виртуально-интеллектуальной экономике - Галица, Игорь Александрович (My University, 2017)
В современных условиях формируется виртуально-интеллектуальная экономика. Неизменный спутник виртуально-интеллектуальной экономики - "экономика стресса", когда качественные скачки приобретают постоянный характер. В условиях виртуальноинтелектуальнои экономики и "экономики стресса" создается принципиально новая система стратегических закономерностей управления, в частности: сокращение "жизненных циклов" знаний, диверсификация знаний, сокращение лага для принятия и реализации управленческих решений, увеличение системности современного производства, уплотнения наполненности развития и тому подобное. It was shown in the process research that in modern conditionsis formed virtual intellectual economy. This economy is characterized by virtualization of economic life, growth of specific gravity predominantly intellectual spheres of management in the total volume of spheres of management, growth of the volume of intellectual operations in non-intellectual spheres of management. In the virtual intellectual economy, the companion is the “economy of stress”, in which qualitative leaps acquire a permanent character. A new system of strategic patterns of enterprise management is formed in the virtual-intellectual economy and “economy of stress”, in particular-reduction “Life cycles” of knowledge, diversification of knowledge, reduction time for adoption and implementation of managerial solutions, increasing systemic of production, compaction of developmental events and so on.
Keywords: кафедра економіки праці та менеджменту; виртуально-интеллектуальная экономика; экономика стресса; стратегические изменения управления предприятием; strategic changes in enterprise management; virtual intellectual economy; economy of stress